Phytase Producing Fungi and Their Efficiency in Hydrolyzing Phytin-P Compounds - Yadva, B K; Tarafdar, J C; Panwar, J; Yadav, R S (Annals of Arid Zone, 2016)
Five most efficient phytase producing fungi belonging to genus Aspergillus, Emericella,Gliocladium, Penicillium and Trichoderma were isolated from arid and semi-arid soils and testedfor their efficiency in hydrolyzing phytin-P compounds. Penicilliul11 purpurogellul11 accumulatedmore biomass closely followed by Trichoderma harzianum during the growth period. A strongnegative correlation (r = - 0.91, n = 20, P